Chapter 12: Capsules (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
AuthorMr. Gourab SahaAssistant Professor, College of Pharmaceutical Sciences, Berhampur, Ganjam, Odisha, IndiaAbstract: Capsules are versatile solid dosage forms that offer unique advantages in drug delivery and patient acceptance. This section covers both hard and soft gelatin capsules, exploring their composition, manufacturing processes, and applications. The properties of gelatin and alternative shell materials, including vegetable-based and hydroxypropyl methylcellulose (HPMC) capsules, are discussed in relation to their impact on drug stability and release. Capsule filling processes for powders, granules, pellets, and liquids are examined, including manual, semi-automatic, and fully automatic filling methods. The formulation considerations for capsule contents, including powder flow properties and compatibility with shell materials, are addressed. Modified-release capsule technologies, such as multi-particulate systems and liquid-filled hard gelatin capsules, are explored for their role in controlled drug delivery. Quality control tests specific to capsules, including weight variation, disintegration, dissolution, and content uniformity, are outlined. Common capsule defects, their causes, and prevention strategies are discussed to ensure product quality. The advantages of capsules in terms of taste masking, ease of swallowing, and potential for combination products are highlighted.Keywords: Gelatin, Encapsulation, Fill material, Dissolution, Modified release, Quality controlView PDF